Role of miRNAs in skeletal muscle aging - Zheng Y (Dove Medical Press, 2018)
Yan Zheng,1,* Jian Kong,1,* Qun Li,2 Yan Wang,1 Jie Li1 1Department of Geriatrics, The First Hospital of Jilin University, Changchun 130021, Jilin, China; 2Department of Thyroid Surgery, The First Hospital of Jilin University, Changchun 130021, Jilin, China *These authors contributed equally to this work Purpose: The aim of this study was to explore the role of miRNAs in the process of skeletal muscle aging. Materials and methods: We analyzed the miRNA microarray datasets from 19 young and 17 old skeletal muscle samples by bioinformatic analysis. Differentially expressed miRNAs were identified, followed by function and pathway enrichment analysis. The expression of miRNAs were validated by real-time quantitative PCR (RT-qPCR) analysis. Results: A total of 23 miRNAs were found to be differentially expressed in old muscle samples based on two platforms. Gene targets of upregulated miRNAs were significantly enriched in the oxytocin signaling pathway, AMP-activated protein kinase (AMPK) signaling pathway, and Notch signaling pathway. The target genes of downregulated miRNAs were significantly related to gap junction, salivary secretion, and estrogen signaling pathway. has-miR-19a and hsa-miR-34a were significant nodes in the miRNA regulatory network. has-miR-19a was closely related to the AMPK signaling pathway. hsa-miR-34a was closely related to cellular senescence and mitogen-activated protein kinase (MAPK) signaling pathway. PCR analysis showed that the expression of has-miR-34a-5p and has-miR-449b-5p was significantly higher in the patient group than in the control group, while no significant difference was observed in the expression of has-miR-19a-3p and has-miR-144-3p between the two groups. Furthermore, the expression of key target genes involved in cellular senescence (sirtuin 1 [SITRI]), MAPK signaling pathway (vascular endothelial growth factor A [VEGFA]), and AMPK signaling pathway (protein kinase AMP-activated catalytic subunit alpha 1 [PRKAA1] and 6-phosphofructo-2-kinase/fructose-2,6-biphosphatase 3 [PFKFB3]) were significantly increased in patients with sarcopenia. Conclusion: has-miR-19a and hsa-miR-34a may play regulatory roles in the aging process of skeletal muscles and may be candidate targets to prevent muscle aging. Further experimental validations are warranted. Keywords: skeletal muscle aging, differentially expressed miRNA, pathway, miRNA regulatory network